AN ANALYSIS ON STUDENTS’ SELF CONFIDENCE IN SPEAKING SKILL - Diyan Febriyani; Desi Sri Astuti; Elly - Syahadati (XXXX-XXXX, 2020)
The the purposes of the research 1) to find out the level of confidence of the eighth grade students' confidence in MTs AL JIHAD Pontianak in the Academic Year of 2019/2020. 2) to find out analysis score of students' confidence in speaking skills to eighth grade MTs AL-JIHAD Pontianak in Academic Year of 2019/2020. The research method used in this research was descriptive method. Data collection techniques used in this research  resume are indirect communication and structured interviews. Data collection tools are questionnaires and interviews. Based on the results of the study can be concluded that in a manner general self-confidence of eighth grade MTs AL-JIHAD Pontianak in Academic Year 2019/2020 has been particularly good more specifically can be described as follows. 1) The level of confidence of the eighth grade students' confidence in MTs AL JIHAD Pontianak in the Academic Year of 2019/2020 namely having a fairly good level of confidence this is evident from the results acquisition of 62% included in the category quite good.  2).students' self-level scores in speaking skills to eighth grade MTs AL-JIHAD Pontianak in Academic Year 2019/2020 is the result of confidence indicator items in can already have a pretty good confidence this can be seen from .some indicators, namely to ask questions in learning 57%, Expressing their own ideas 61%, Appreciating the opinions of others 59%, Working together 66%, Open to criticism 71%, Optimistic 54%, Daring to present 63%. Suggestions after this research are conducted, which are 1). Students can further increase their confidence through working with the teacher through the provision of facilities that are necessary to carry out. 2) The teacher helps students to increase their confidence in speaking ability through activities that can support students in improving their speaking ability. Keywords : Self Confidence, Speaking Skills